Procedure for Restoration of Environmental Damage resulting from Non-point Source Emissions - Salma, Marija (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
The paper examines the notion of non-point source emission as well as legal methods, procedures, for restoration of environmental damage. It is pointed out that non-point source pollution is generated from several polluters. Joint activity of polluters calls for measures of ecological restoration, instead of tort proceedings. However, non-point source emissions may result in standard case tort provided human health is affected, lives are lost or property is damaged or destroyed. In this article two types of tort proceedings are being examined: those initiated by an action for elimination of the source of pollution, when the environmental risk is emerging and an action for compensation of damages, when the damage has already occurred, prior to the action being filed. Further, the author points to the problem of causation given that with non-point emissions each individual act of emission does not cause damage by itself; however it contributes to an emergence of damage in joint activity with other emissions. For these reasons, lawmakers opted for joint and severe liability in cases of non-point emissions.